ЭПИДЕМИОЛОГИЧЕСКИЕ ОСОБЕННОСТИ АРТЕРИАЛЬНОЙ ГИПЕРТОНИИ ПРИ ХРОНИЧЕСКОЙ СЕРДЕЧНОЙ НЕДОСТАТОЧНОСТИ - Е. Г. Артемьева; Е. В. Фролова (SINAPS LLC, 2014)
The results of the epidemiological research obtained on the territory of Chuvash Republic are presonted. The prevalence of arterial hypertension among the patients, sufferring from chronic heart failure was analyzed. The representative method in Chuvash Republic had proven the high prevalence (100%) of arterial hypertension in patients with inveterate cardiac decompensation. It was also established that arterial hypertension III has the same prevalence rate among both the population and the representative group. However, the severity of arterial hypertension correlates with the severity of inveterate cardiac decompensation, while the prevalence rate of arterial hypertension III is much higher among men than among women.